HUBUNGAN PENGETAHUAN DAN STRES DENGAN TINGKAT KEPARAHAN ASMA BRONKHIAL DI RS FADHILAH - Esti, Amira; Oktorina, Rola; Sari, Yade Kurnia; Tamala, Evi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Bronchial asthma is not only a public health problem in developed countries but also occurs in developing countries. The death rate from asthma worldwide is estimated to increase by 20% in the next 10 years if not properly controlled. Theaim of this study was to examine the relationship between knowledge and stress with the severity of bronchial asthma This type of research is quantitative using a cross sectional design with a sample size of 52 respondents conducted, with a sampling technique using Total Sampling. Data measurement tools use questionnaires and checklists, and are analyzed using univariate and bivariate data analysis. The research results showed that more than half of the respondents (57.7%) experienced severe bronchial asthma, more than half of the respondents (55.8%) had low knowledge about bronchial asthma and more than half of the respondents (51.9%) experienced stress. Based on bivariate analysis, the results showed that there was a relationship between knowledge and stress and the severity of bronchial asthma with a P value = 0.033 and 0.028. It was concluded that knowledge and stress were related to the severity of bronchial asthma. It is hoped that this research can be used as a source of information for health workers so that they can pay attention to people's knowledge and stress levels about bronchial asthma so that with good knowledge and low stress levels they can reduce the severity of bronchial asthmaKeywords : Bronchial Asthma, Knowledge, Stress